Practical design of ships and other floating structures proceedings of the Eighth International Symposium on Practical Design of Ships and Other Floating Structures, 16-21 September, 2001, Shanghai, China - Wu, You-Sheng; Cui, Wei-Cheng; Zhou, Guo-Jun (Elsevier, 2001)
This proceedings contains the papers presented at The 8th International Symposium on Practical Design of Ships and Other Floating Structures held in China in September 2001 - the first PRADS of the 21st Century. The overall aim of PRADS symposia is to advance the design of ships and other floating structures as a professional discipline and science by exchanging knowledge and promoting discussion of relevant topics in the fields of naval architecture and marine and offshore engineering. In line with the aim, in welcoming the new era, this Symposium is intended to increase international co-operation and give a momentum for the new development of design and production technology of ships and other floating structures for efficiency, economy, safety, and environmental production. The main themes of this Symposium are Design Synthesis, Production, Hydrodynamics, Structures and Materials of Ships and Floating Systems. Proposals for over 270 papers from 26 countries and regions within the themes were received for PRADS 2001, and about 170 papers were accepted for presentation at the symposium. With the high quality of the proposed papers the Local Organising Committee had a difficult task to make a balanced selection and to control the total number of papers for fitting into the allocated time schedule approved by the Standing Committee of PRADS. Volume I covers design synthesis, production and part of hydrodynamics. Volume II contains the rest of hydrodynamics, and structures and materials.
Keywords: Naval architecture -- Congresses.; elektronické knihy; electronic books